Circulating miRNAs Are Associated with the Systemic Extent of Atherosclerosis: Novel Observations for miR-27b and miR-146 - Pereira-da-Silva, Tiago (2021)
The mechanisms that regulate the systemic extent of atherosclerosis are not fully understood. We investigated whether the expression of circulating miRNAs is associated with the extent of stable atherosclerosis to a single territory or multiple territories (polyvascular) and with the severity of atherosclerosis in each territory. Ninety-four participants were prospectively recruited and divided into five age- and sex-matched groups: presenting no atherosclerosis, isolated coronary atherosclerosis, coronary and lower extremity atherosclerosis, coronary and carotid atherosclerosis, and atherosclerosis of the coronary, lower extremity, and carotid territories. The expression of six circulating miRNAs with distinct biological roles was assessed. The expression of miR-27b and miR-146 differed across groups (p < 0.05), showing a decrease in the presence of atherosclerosis, particularly in the three territories. miR-27b and miR-146 expression decreased in association with a higher severity of coronary, lower extremity, and carotid atherosclerosis. Polyvascular atherosclerosis involving the three territories was independently associated with a decreased miR-27b and miR-146 expression. Both miRNAs presented an area under the curve of >= 0.75 for predicting polyvascular atherosclerosis involving the three territories. To conclude, miR-27b and miR-146 were associated with the presence of severe polyvascular atherosclerosis and with the atherosclerosis severity in each territory. Both are potential biomarkers of severe systemic atherosclerosis.